Strategi Pemasaran Kartu Kredit PT. Bank Negara Indonesia (Persero)Tbk. Kantor Cabang Maumere - Yoseph Nong Adi Suryo; Yoseph D. P. Rangga; Nunsio Handrian Meylano (Universitas Nusa Nipa Maumere, 2025)
This study aims to find out what factors are supporting and inhibiting in the credit card marketing process and to find out the marketing strategies carried out by the marketing staff of PT. Bank Negara Indonesia (Persero) Tbk, Maumere Branch Office in promoting or marketing credit card products. The design of this study uses a qualitative approach to understand the credit card marketing strategy in PT. Bank Negara Indonesia (Persero) Tbk, Maumere Branch Office. Data were collected through interviews and analyzed qualitatively. Based on the results of the study, it can be seen that credit card marketing is supported by factors such as a wide merchant network, ease of application, and effective marketing strategies, but is faced with challenges such as limited merchants in certain regions, low financial literacy, and competition with digital payment methods. Through Kearns' SWOT analysis, BNI Maumere Branch can implement the SO strategy by leveraging its strengths to seize opportunities, such as expanding cooperation with the education and tourism sectors and offering locally-based reward programs. The WO strategy is focused on improving financial literacy and incentives for small merchants. ST's strategy is used to strengthen customer service and highlight product excellence in the face of digital competition, while WT's strategy focuses on reducing costs and increasing transparency to attract more customers and strengthen competitiveness in the market.